HUBUNGAN KEKUATAN OTOT LENGAN DAN KESEIMBANGAN TERHADAP KEMAMPUAN SIKAP LILIN DALAM SENAM LANTAI SISWI KELAS X SMK NEGERI 2 BONE - Saputri, Reni; Khalid Rijaluddin; Andi Mutmainna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the relationship between arm muscle strength and balance with the ability to perform the candle stand in floor gymnastics among tenth-grade female students at SMK Negeri 2 Bone. This study was motivated by the difficulties experienced by students in performing the candle stand movement correctly and stably. The research used a quantitative approach with a correlational design. The population consisted of 32 tenth-grade students, with 22 female students selected as the sample using purposive sampling. Data were collected through a push-up test to measure arm muscle strength, the standing stork stand test to measure balance, and a candle stand test to assess candle stand ability. Data were analyzed using descriptive statistics, normality and homogeneity tests, and hypothesis testing with SPSS. The results showed a significant relationship between arm muscle strength and candle stand ability, with R = 0.625 and p = 0.002 < 0.05. Balance also had a significant relationship with candle stand ability, with R = 0.611 and p = 0.003 < 0.05. Simultaneously, arm muscle strength and balance had a significant relationship with candle stand ability, with R = 0.683 and p = 0.003 < 0.05. Thus, arm muscle strength and balance are significantly related to the ability to perform the candle stand in floor gymnastics among tenth-grade female students at SMK Negeri 2 Bone.